Hydroxyl Radical Generation and DNA Nuclease Activity: A Mechanistic Study Based on a Surface‐Immobilized Copper Thioether Clip‐Phen Derivative. Issue 29 (16th June 2016) - Romo, Adolfo I. B.; Abreu, Dieric S.; de F. Paulo, Tércio; Carepo, Marta S. P.; Sousa, Eduardo H. S.; Lemus, Luis; Aliaga, Carolina; Batista, Alzir A.; Nascimento, Otaciro R.; Abruña, Héctor D.; Diógenes, Izaura C. N.
Abstract: Coordination compounds of copper have been invoked as major actors in processes involving the reduction of molecular oxygen, mostly with the generation of radical species the assignment for which has, so far, not been fully addressed. In the present work, we have carried out studies in solution and on surfaces to gain insights into the nature of the radical oxygen species (ROS) generated by a copper(II) coordination compound containing a thioether clip‐phen derivative, 1, 3‐bis(1, 10‐phenanthrolin‐2‐yloxy)‐ N ‐(4‐(methylthio)benzylidene)propan‐2‐amine (2CP‐Bz‐SMe), enabling its adsorption/immobilization to gold surfaces. Whereas surface plasmon resonance (SPR) and electrochemistry of the adsorbed complex indicated the formation of a dimeric Cu I intermediate containing molecular oxygen as a bridging ligand, scanning electrochemical microscopy (SECM) and nuclease assays pointed to the generation of a ROS species. Electron paramagnetic resonance (EPR) data reinforced such conclusions, indicating that radical production was dependent on the amount of oxygen and H2 O2, thus pointing to a mechanism involving a Fenton‐like reaction that results in the production of OH . . Abstract : Probing a radical idea : Studies in solution and on surfaces (SECM and SPR) of a Cu II coordination compound containing a clip‐phen derivative indicated the production of OH . radicals through a catalytic mechanism involving a Fenton‐like reaction with the formation of a dimeric Cu I intermediate containing O2 as a bridging ligand and the recovery of the starting Cu II complex (see figure).